Integrating Interfaith Dialogue and Economic Empowerment: A Study on Interfaith Women Community Srili Yogyakarta - Wiwin Siti Aminah Rohmawati; Kamilia Hamidah; Erin Gayatri (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
The COVID-19 pandemic has affected nearly every aspect of life, particularly in the economic sector and micro, small, and medium enterprises (MSMEs) — the vast majority of whom are women. Women are also among the most vulnerable populations to the COVID-19 pandemic. Srikandi Lintas Iman (SRILI) is a women’s community that has been doing interfaith dialogue since 2015. SRILI has been and continues to carry out economic empowerment of ummah to strengthen interfaith women’s solidarity in the face of the COVID-19 pandemic. One of SRILI’s economic empowerment projects is the management of the Srili Bakoelan Online Market and the Nglarisi Dagangan Teman (buying friend’s products) movement through social media. This is qualitative research aimed at addressing two major questions: how to approach and organize the program and how it promotes the personal transformation of the SRILI Bakoelan community as well as the development of creative economic potential in the family and religious communities. The findings of the study indicate that social solidarity, social linking, and social bonding are valuable assets that a community may use to always be adaptive in providing a place for interfaith dialogue and response to social problems.